Peran perempuan masa kini : menggebrak batas di era revolusi industri 4.0 dan era society 5.0 - Ameilia, Mufidatul (Maliki Interdisciplinary Journal, 2024)
This study aims to understand how the role and contribution of women today in the era of the Industrial Revolution 4.0 and the era of society 5.0. Her presence should be used as well as possible, because that era promised the position of women to be part of world civilization. The method used in this study is a comparative approach, where researchers discuss how globalization and technological advances in this era affect the role of women. The result of this research is to provide awareness for women out there to play a role in building civilization through examples of inspiring figures and various achievements. In addition, to provide education that the position of women should not be underestimated, awareness of gender equality between men and women is needed in this regard.